THE CORRELATION OF CHARACTERISTIC RESPONDENTS THROUGH KNOWLEDGE AND ATTITUDES OF DIABETICS ABOUT FOOT CARES AT NTB PUBLIC HOSPITAL DEPARTMENT OF INTERNAL MEDICINE IN 2014 - Aan Dwi Sentana (Jurnal Kesehatan Prima, 2016)
Abstract: The patients’ foot care with diabetes which is fine, that is by checking your foot everyday, especially the sole of foot, toes, toenails care and foot skin care, shoes should be worn according to the shape and size of the foot and diabetic feet gymnastics. Based on the data which obtained from NTB Public Hospital, Medical Record Room at the patient unit in 2013 found that there were 93 patients who suffered gangrene. The research aimed to find out how knowledge and attitudes of diabetics about foot cares in the department of internal medicine at NTB Public Hospital in 2014. This research had been conducted at NTB Public Hospital Department of Internal Medicine with descriptive method. Population in this study were 40 patients who suffered diabetes. The sample collection was conducted with non probability sampling and it used accidental sampling methods. The research instrument was questionnaire. The finding in this research indicated that the most knowledge included in the category of excellent was 20 respondents (50.00%), sufficient category was 17respondents (42.50%), and minority was 3 respondents (7.50%). Meanwhile, most of patients’ attitude was positive category (favorable) by 25 respondents (62.5%) and other were negative (unfavorable) as many as 15 respondents (37.5%) whereas Spearmen test found a significant correlation in terms of characteristics respondents (age, education, occupation, resources) with knowledge and attitude. Therefore, it was expected that respondents who suffered diabetes mellitus regulary check and be concerned of the foot, thus there will not be gangrene caused by diabetes mellitus and respondents should extend their knowledge by reading books or magazines and other sources of information which relate to diabetes mellitus.